2011
DOI: 10.1007/s10592-011-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and genetic status of an isolated population of bog turtles (Glyptemys muhlenbergii): implications for managing small populations of long-lived animals

Abstract: In this study, we sought to determine the population stability and genetic diversity of one isolated population of the federally-threatened bog turtle (Glyptemys muhlenbergii) in North Carolina. Using capture-recapture data, we estimated adult survival and population growth rate from 1992 to 2007. We found that the population decreased from an estimated 36 adult turtles in 1994 to approximately 11 adult turtles in 2007. We found a constant adult survival of 0.893 (SE = 0.018, 95% confidence interval, 0.853-0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 60 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…At Site 2, survival rates and population sizes declined over the 16-yr study period, consistent with an increase in low-quality habitat. Survival rate estimates of Bog Turtle at these sites were similar to survival rates and population sizes of other northern Bog Turtle populations (Pittman et al, 2011; and other long-lived, northern turtle species (Congdon et al, 1993(Congdon et al, , 1994Litzgus, 2006). However, survival rates at Site 2 in 2009 were lower than any other Bog Turtle studies reported.…”
Section: Discussionsupporting
confidence: 62%
“…At Site 2, survival rates and population sizes declined over the 16-yr study period, consistent with an increase in low-quality habitat. Survival rate estimates of Bog Turtle at these sites were similar to survival rates and population sizes of other northern Bog Turtle populations (Pittman et al, 2011; and other long-lived, northern turtle species (Congdon et al, 1993(Congdon et al, , 1994Litzgus, 2006). However, survival rates at Site 2 in 2009 were lower than any other Bog Turtle studies reported.…”
Section: Discussionsupporting
confidence: 62%
“…In all three cases, bottlenecked populations are still vulnerable and incorrect conclusions about the genetic health of threatened populations can slow recovery efforts. We recommend caution when considering previous conclusions that populations of long-lived organisms such as turtles are not genetically impacted by bottlenecks (e.g., Kuo and Janzen, 2004;Mockford et al 2005;Marsack and Swanson 2009;Spradling et al 2010;Pittman et al 2011). These conclusions should be re-evaluated as more appropriate tests become available.…”
Section: Bottleneck Tests and Long-lived Organismsmentioning
confidence: 86%
“…The expected genetic effects of recent, anthropogenic habitat and population fragmentation have not been detected in several turtle species, despite empirical and anecdotal evidence of significant population declines and fragmentation (Rubin et al 2001;Kuo and Janzen 2004;Marsack and Swanson 2009;Pittman et al 2011). Isolated subpopulations remain genetically identical over many years even when dispersal is severely restricted (Rubin et al 2001;Bennett et al 2010), apparently owing to their long generation times.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations